PEMAHAMAN KHILAFAH DAN INTERNALISASINYA DALAM JEMAAT AHMADIYAH GONDRONG TANGERANG BANTEN: (Studi Living Qur’an) - Adrika Fithrotul Aini; Ahmad Suhendra (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
Ahmadi is an Islamic group based in India. The group stressed the aspects of ideological-eschatological because this group is mahdiistik with the belief that the al-Mahdi viewed as “Judge Peng-Islah” or as a “peacemaker”. Al-Mahdi in the Ahmadiyya faith was Mirza Ghulam Ahmad, who has the task to reunite the split Muslims, both in the field of faith and the Shari’a. Of belief, jema’at this very rapidly growing in Indonesia. As this church already exists in various regions in Indonesia, such as the Ahmadiyah in Gondrong Tangerang, Banten (JAG). This study examines the understanding of the concept of the caliphate in members of Ahmadiyah. This research is a field, namely the phenomenon of living Quran. which will lead to a study that examines the living Quran verses of the Koran understanding of the concept of the caliphate held by JAG, and also internalization in their daily lives are realized in a variety of receptions, both hermeneutic, aesthetic, and cultural. Sociological approach to the theory of Pierre Bourdieu’s habitus become a foothold in this paper. Understanding the concept of the caliphate is the basis of understanding and JAG members have internalized that manifested itself in several ways, namely solidarity, unity, sacrifice, and social.